PENGARUH PEMBAGIAN KERJA TERHADAP PENINGKATAN EFISIENSI KERJA KARYAWAN PASTRY DI HOTEL SANTIKA PREMIERE MALANG - Estikowati Estikowati (Universitas Merdeka Malang, 2017)
The study was conducted to determine the effect of the division of labor on the work efficiency of pastry employees at Hotel Santika Premiere Malang. Work efficiency relates to the product produced with the resources used. While the division of labor is a separator type of work done by individuals. Researchers used the Simple Linear Regression Analyze method to predict how far the value of the dependent variable will be changed if the independent variable is changed. From result of research of independent variable (X) that is Division of labor and dependent variable (Y) Work efficiency have significant relation. This is evidenced from the data processing is known significant value sebersar 0.003 0.05, with the conclusion Ho rejected and Ha accepted that there is influence between the Division of labor (X) on Efficiency of work. From the questionnaire data the authors conclude that the existing division of labor is not appropriate for employees so that the level of efficiency of employees decreased.The study was conducted to determine the effect of the division of labor on the work efficiency of pastry employees at Hotel Santika Premiere Malang. Work efficiency relates to the product produced with the resources used. While the division of labor is a separator type of work done by individuals. Researchers used the Simple Linear Regression Analyze method to predict how far the value of the dependent variable will be changed if the independent variable is changed. From result of research of independent variable (X) that is Division of labor and dependent variable (Y) Work efficiency have significant relation. This is evidenced from the data processing is known significant value sebersar 0.003 0.05, with the conclusion Ho rejected and Ha accepted that there is influence between the Division of labor (X) on Efficiency of work. From the questionnaire data the authors conclude that the existing division of labor is not appropriate for employees so that the level of efficiency of employees decreased.